PH, alkalinity, temperature, salinity and other variables collected from discrete sample and profile observations using Alkalinity titrator, CTD and other instruments from Sarmiento de Gamboa in the North Atlantic Ocean from 2011-01-28 to 2011-03-14 (NCEI Accession 0144248) - Hernandez-Guerra, Alonso; Hernandez-Guerra, A., F. Perez, A. Rios, E. Guallart, X. Padin and M. Vazquez-Rodriguez (NOAA NCEI Environmental Data Archive, 2016)
NCEI Accession 0144248 includes discrete sample and profile data collected from Sarmiento de Gamboa in the North Atlantic Ocean from 2011-01-28 to 2011-03-14. These data include DISSOLVED OXYGEN, HYDROSTATIC PRESSURE, NITRATE, Potential temperature (theta), SALINITY, TOTAL ALKALINITY (TA), WATER TEMPERATURE, pH, phosphate and silicate. The instruments used to collect these data include Alkalinity titrator, CTD, bottle and spectrophotometer. These data were collected by Fiz Perez and Aida F. Rios of Instituto de Investigaciones Marinas de Vigo and Alonso Hernandez-Guerra of Universidad de Las Palmas de Gran Canaria as part of the CLIVAR_A05_29AH20110128 data set. CDIAC associated the following cruise ID(s) with this data set: 24N_Malaspina_2011 The International CLIVAR Global Ocean Carbon and Repeat Hydrography Program carries out a systematic and global re-occupation of select WOCE/JGOFS hydrographic sections to quantify changes in storage and transport of heat, fresh water, carbon dioxide (CO2), and related parameters.